Explaining and questioning - Kerry, Trevor (London : Nelson Thornes ltd., 2005)
Offering practical support, this invaluable series of books combine background theory with realistic advice, with links to the government based standards framework. Activities, taken from real-life examples, help users to implement and develop practical skills.
Includes index.
Keywords: Effective teaching; Communication in education; Explanation; Questioning